Determination of the concentration of inoculo and time of fermentation, utilizing microbiota of the kefir grains as biological agent and serum of milk as substrate - Arévalo Ortiz, Humberto F. (2008)
The time of fermentation was determined simultaneously and the concentration of the inocule required, obtaining so much the time of fermentation as the concentration of the inocule, because this estudy's objetive was to determine the smaller time of fermentation with a maximum yield of biomass. Microbiota was used of Grains of Kefir like biological agent, as it is a mixture symbiotic of bacteria and yeasts. The concentrations that were used of the inocule were of 2%, 3%, 4%, 5%, 6%,7% and 8%. Also one determined the extreme values of pH, density and content of sugars totals that were reached in average of culture, thus to be able to determine full stop of the fermentation. The results indicated that the concentration of the inocule optimal corresponds to 4 % the same that corresponds to optimal time of fermentation of 48 hours.